Instytucjonalne relacje państwo–Kościół w Rumunii jako przykład modelu przyjaznej separacji - Kamiński, Konrad (Studia Prawa Publicznego, 2025)
The aim of this article is to provide a detailed analysis of the fundamental principles of the state-church relationship model in the Republic of Romania, which can be classiﬁed as a speciﬁc model of friendly separation. This model is based on a balance between the formal separation of state and religious institutions and the possibility of state support for religious activities in areas such as education, culture and social welfare. A signiﬁcant element of the Romanian model is its acknowledgment of the historical and cultural role of the Romanian Orthodox Church, which holds a prominent position in shaping Romanians’ national identity and public life. The Church plays a crucial role in maintaining social bonds and transmitting the nation’s heritage. The article also highlights unique features of the Romanian model, such as its three-tier legal classiﬁcation system for religious communities, which differentiates the legal status of registered denominations, religious associations, and religious groups. This system, combined with the historical signiﬁcance of Orthodoxy, gives the Romanian model distinctive characteristics that set it apart from other countries implementing a model of friendly separation, an example being Poland. The analysis demonstrates how local historical, cultural and social conditions inﬂuence the development of Romania’s speciﬁc version of the friendly separation model. The author argues that although the autonomy of both spheres is formally maintained, cooperation between the state and recognized religious communities (particularly the Romanian Orthodox Church) is essential for the fulﬁllment of many public tasks, especially in areas requiring the fostering of national unity.